The Role of Banks in Attracting Investments - Eshmurodova, S. U.; Ilxomov, Q. Yo. (Research Parks Publishers, 2023)
This article discusses about the role of investment in the country's economy and the role of banks in attracting investments ,in addition to, Conclusions and suggestions are also given about the importance of bank investments in the economy.